2013
DOI: 10.1007/s00167-013-2643-4
|View full text |Cite
|
Sign up to set email alerts
|

The arcuate ligament revisited: role of the posterolateral structures in providing static stability in the knee joint

Abstract: Among the different structures of the posterolateral corner, only the arcuate ligament has a significant role in restricting excessive primary and coupled external rotation. The popliteus muscle-tendon unit is not a primary static stabilizer to tibial external rotation at 90° of knee flexion. The posterior cruciate ligament is the primary restraint to excessive recurvatum and posterior tibial translation. The posterior cruciate ligament and the arcuate ligament have predominant role for the posterolateral stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 28 publications
4
40
0
1
Order By: Relevance
“…This good control of both components of posterolateral instability despite differing reconstruction techniques is borne out by the literature: e.g., Yang et al [25] using the Larson technique, and Tardy et al [26] using anatomic reconstruction. It is, thus, not possible to conclude in favor of anatomic reconstruction, in agreement with Thaunat et al [27].…”
Section: Discussionsupporting
confidence: 80%
“…This good control of both components of posterolateral instability despite differing reconstruction techniques is borne out by the literature: e.g., Yang et al [25] using the Larson technique, and Tardy et al [26] using anatomic reconstruction. It is, thus, not possible to conclude in favor of anatomic reconstruction, in agreement with Thaunat et al [27].…”
Section: Discussionsupporting
confidence: 80%
“…Anatomically, we found the ALL during dissection of the posterolateral corner, with results published in Thaunat et al 9 At that time, we found that the ALL was very close to the lateral epicondyle with a large insertion area. After this, we were cautious with the different anatomic descriptions distal to the lateral epicondyle, as described by Vincent et al, 10 Claes et al, 1 and Helito et al, 4 or proximal to the lateral epicondyle, as described by Dodds et al 2 Finally, we performed a cadaveric study on 52 knees for analysis of the femoral insertion of the ALL (Daggett et al, unpublished data, June 2015).…”
supporting
confidence: 83%
“…Ce bon contrôle des deux composantes de la laxité postéro-latérale malgré des modalités de reconstruction différentes est également souligné dans la littérature, comme le montrent Yang et al [25] en utilisant une plastie de type Larson ou Tardy et al [26] utilisant une plastie anatomique. Il ne nous est donc pas possible de conclure à la supériorité des plasties anatomique, ce qui est conforme aux résultats de Thaunat et al [27].…”
Section: Discussionunclassified